Research in International Transfer of Vocational Education and Training – A Systematic Literature Review - Toepper, Miriam; Zlatkin-Troitschanskaia, Olga; Kühling-Thees, Carla (International Journal for Research in Vocational Education and Training, 2021)
Context: The transfer of vocational education and training (VET) has a long tradition and can be based on various conceptual and methodical approaches. Transfer process and success can be influenced by numerous factors at different levels (systemic, institutional and individual). However, the existing research on the challenges and success factors of VET transfer is very heterogenous and fragmented. Method: To provide a comprehensive and structured overview of the current state of the international research on transfer in the context of VET, we conducted a literature review, which is presented here. Using the method of systematic literature review, a total of 231 studies were found and 41 studies were selected based on the defined criteria for full text analysis. Findings: Various specific research foci and analytical approaches used on the included studies were identified and documented. The transfer of a dual VET system or its elements is based on different approaches and perspectives of the recipient country and the transferee. Major challenges for the transfer of dual VET systems include the social reputation of VET in the recipient countries and (language- and culture-related) communication difficulties between the involved parties. For a successful transfer of VET, a deeper knowledge of the contextual conditions in the recipient country are of particular importance, as well as a close, longstanding cooperation between the involved parties. Conclusion: The generated knowledge about key contextual conditions at the individual, company and systemic level in the context of VET transfer can provide a valuable basis for future VET cooperation.